Motivasi belajar santriwan dan santriwati: Adakah peranan efikasi diri akademik dan dukungan orang tua? - Halimatus Sa'diyah; Andik Matulessy; Nindia Pratitis (INNER: Journal of Psychological Research, 2023)
Abstract This research was conducted to determine the relationship between academic self-efficacy and parental support for learning motivation. It is quantitative in nature with a correlational type. The population in this study was 162 students and MTs students at PPDS Kejapanan. The number of study participants was 115, obtained through a simple random sampling technique. The research instrument consists of a learning motivation scale, an academic self-efficacy scale, and a parental support scale. Data analysis using multiple regression analysis found that academic self-efficacy and parental support simultaneously influenced learning motivation. As for partial, there is a significant influence between academic self-efficacy on learning motivation and no influence of parental support on learning motivation. This can be interpreted to mean that high academic self-efficacy will be in the same direction as the level of learning motivation, while parental support has no effect on the learning motivation of the research subject. Nevertheless, together academic self-efficacy and parental support have a significant relationship with learning motivation. Keywords: Parental Support; Academic Self-Efficacy; Learning motivation; Male and Female Student.